Calculation of Age Requirements for Regional Head Candidates in Indonesia (Comparative Study of Supreme Court an Constitutional Court Decisions) - Khulaili, Rabith Madah; Latowale, Mohamad Irfan; Korua, Verry; Ramadhan, Rahmat Syahrul; Tinambunan, Hezron Sabar Rotua (Riwayat: Educational Journal of History and Humanities, 2024)
This study is a qualitative study with a normative juridical approach, namely an approach that relies on laws and regulations as the main material to provide arguments for the hypotheses and perspectives that researchers present. The data used in this article are secondary data that researchers obtain from various credible sources, namely laws and regulations. The data used are analyzed using comparative legal interpretation techniques with the interpretation results below.